Argon laser photocoagulation of symptomatic flap tears and retinal breaks of fellow eyes. Issue 7 (July 1981) - Pollak, A; Oliver, M
Abstract : A series of 95 eyes (93 patients) with retinal breaks, high-risk candidates for rhegmatogenous retinal detachment, were treated prophylactically with argon laser photocoagulation (ALP). Group A comprised 74 eyes with flap symptomatic tears. In 28 of these (subgroup A (1)) the size of the tear was smaller than 1 disc diameter and greater than 1/3 disc diameter. In 46 eyes (subgroup A (2)) the size of the tear was at least 1 disc diameter but not greater than 3 disc diameters. Group B comprised 21 fellow eyes with 34 retinal breaks in patients who had retinal detachment in the other eye. One patient of subgroup A (1) developed a rhegmatogenous retinal detachment 6 days after ALP treatment. One patient of group B developed a retinal detachment after cataract extraction. This detachment was unrelated to the previously treated retinal break. In the series of group A the mean follow-up period was 27.8 months. From previously reported follow-up data it is probable that at least in the case of flap symptomatic tears our results can be considered conclusive. There were no complications related to the prophylactic treatment of dangerous retinal breaks with ALP. This form of treatment is accurate, easy to use, and comfortable for the patient. ALP would appear to be superior to xenon arc photocoagulation and cryopexy.